Pitts, M.; Versluys, J. (eds.) (2015): Globalisation and the Roman World: world history, connectivity and material culture - Machuca Prieto, Francisco (SPAL - Revista de Prehistoria y Arqueología, 2017)
Pitts, M.; Versluys, J. (eds.) (2015): Globalisation and the Roman World: world history, connectivity and material culture. Cambridge, Cambrigde University Press, 296 pp. ISBN: 978-1-107-04374-9